Belajar dan Pembelajaran (Pendidikan Dasar) - Annisa Nidaur Rohmah (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2017)
Studying and learning are two concepts that are interconnected, the second is the major activity in education. Learning is interpreted the process of changing behaviour as a result of the interaction of the individual with thoose environments. Behaviour change the result of studying nature continuely, functional, positive, active and through. While learning the interpreted activities process through the stages of planning, implementation and evaluation. This study aims to discuss then theory about the concept of studying and learning in the elemntary school with the hopes of being able to serve as a reference is in finding a breakthrough to increase new teachers and teacher candidates in doing the learning process to the participants teach, until the learning process is not only dominated by the teacher wich in the end caused the participants teach less grow in ability he thinks.